A new bulbil-forming species of Sistotrema (Cantharellales, Hydnaceae) from Brazil - Barreto, Gabriel G.; Cantillo, Taimy; Costa-Rezende, Diogo; Gusmão, Luis F.p. (Phytotaxa, 2023)
During mycological surveys in Floresta Edmundo Navarro de Andrade, Rio Claro province, São Paulo state, a bulbil-forming fungal specimen was collected on dead bark of Eucalyptus grandis. Following morphological and phylogenetic analysis, it was confirmed that the specimen belongs to an undescribed taxon. Phylogenetic analyses of ITS-LSU revealed that our strain is related to Sistotrema coronilla s.l., a recognized bulbil-forming lineage within Hydnaceae and other genera that also produce bulbils. This is the first Sistotrema species recorded on Eucalyptus substrates worldwide. A comprehensive morphological and phylogenetic analysis is presented, and Sistotrema bulbilliferum is described and illustrated.